Evaluation of the efficacy, safety and influencing factors of concomitant and sequential administration of viral respiratory infectious disease vaccines: a systematic review and meta-analysis - Lu, Dafeng; Han, Yifang; Xu, Ruowei; Qin, Mingke; Shi, Jianwei; Zhang, Caihong; Zhang, Jinhai; Ye, Fuqiang; Luo, Zhenghan; Wang, Yuhe; Wang, Chunfang; Wang, Chunhui (Frontiers in Immunology, 2023)
Background: There is no clear conclusion on the immunogenicity and adverse events of concomitant administration the viral respiratory infectious disease vaccines. We aimed to evaluate the impact of concomitant administering viral respiratory infectious disease vaccines on efficiencies, safety and influencing factors.: This meta-analysis included studies from PubMed, Embase, Cochrane Central Register of Clinical Trials, Web of Science, WHO COVID-19 Research, and ClinicalTrials.gov databases. Randomized controlled trials of the adult participants concomitant administered with viral respiratory infectious disease vaccine and other vaccines were included. The main outcomes were the seroconversion rate and seroprotection rate of each vaccine. Used the Mantel-Haenszel fixed effects method as the main analysis to estimate the pooled RRs and the corresponding 95% confidence intervals. The risk of bias for each trial was assessed using the Cochrane Handbook for Systematic Reviews of Interventions, while evidence certainty was evaluated using the Grading of Recommendations Assessment, Development, and Evaluation system. Results: A total of 21 studies comprising 14060 participants with two types of vaccines were retained for the meta-analysis. Concomitant immunization reduced the geometric mean titer (RR: 0.858, 95% CI: (0.785 to 0.939)) and the geometric mean fold rise (0.754 (0.629 to 0.902)) in the SARS-COV-2 vaccine group but increased the seroconversion rate (1.033 (1.0002 to 1.067)) in the seasonal influenza vaccine group. Concomitant administration were influenced by the type of vaccine, adjuvant content, 3 booster immunization, and age and gender of the recipient. Conclusions: This meta-analysis suggested that the short-term protection and safety of concomitant administered were effective. Appropriate adjuvants, health promotion and counselling and booster vaccines could improve the efficiency and safety of Concomitant vaccination Registration: The review protocol was prospectively registered with the PROSPERO ID CRD42022343709.